Complete remission of VZV reactivation treated with valganciclovir in a patient with total lymphocyte depletion and acute kidney injury after allogeneic bone marrow transplantation. - Maximova, Natalia; Antonio, Pizzol; Marilena, Granzotto; Rovere, Francesca; Tamaro, Paolo (APMIS, 2015)
Varicella zoster virus (VZV), a threat for hematopoietic stem cell transplantation (HSCT) recipients, is still one of the most common viral pathogens that affect these patients with a reported incidence ranging between 17% and 50% in the post transplantation period. Valganciclovir (V-GCV), a valine ester pro-drug of GCV orally administrable, has recently shown great activity against CMV infections, but there are no reports of its clinical efficacy against VZV. We here report a case history of a patient with positive serologic test for VZV, who underwent allogeneic HSCT and developed an atypical varicella-like illness. First-line therapy with foscarnet had to be discontinued due rapid development of renal impairment (creatinine: 2.60 mg/dL, urea: 130.6 mg/dL) and therefore was switched to V-GCV. The renal impairment and skin lesions of the patient fully recovered after few days of therapy, even though the patient had complete lymphocyte depletion. This is the first case of a patient with chickenpox-like illness treated successfully with V-GCV.
Keywords: Acute Kidney Injury; Adolescent; Bone Marrow Transplantation; Fatal Outcome; Female; Ganciclovir; Herpes Zoster; Herpesvirus 3, Human; Humans; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Viral Load